Person-centred care for dementia patients (front end Android app) - Tan, Ashley Zhi Ruong (2018)
Singapore has one the fastest ageing population in the Asia-Pacific region and the amount of people living with dementia is expected to double by 2030. Although dementia is commonly known to affect the older population, there is an increase in patients aged 65 and below with dementia [1]. A person-centred care approach has become an increasingly popular approach in giving care to the dementia patients. In the person-centred care approach, the patients are actively involved in the planning phase of their medical treatment. The patient’s preferences are taken into consideration while planning the patient’s treatment. This helps to create a much happier and calm environment for the dementia as they will be able to indicate their likes and dislikes. The person-centred care (PEAR) system has been developed to aid the healthcare personnel in providing better care for the dementia patients. The purpose of this project is to improve on the existing Android application of the PEAR system which is used by caregivers, supervisors and doctors. To improve the efficiency of this application, the application migrated from using direct SQL to API to reduce the latency of retrieving, processing and displaying data on the PEAR Android application. The user interface of the PEAR Android application was also redesigned to provide the users of this application a more pleasant user experience. Research has shown that the attractiveness of an application is one of the factors of how usable the user determines the application to be. An attractive application we perceived as more usable than operating on an unappealing one [2]. Hence, the look and feel of the application has been redesigned to improve the usability for the users.